MUNGKINKAH COVID-19 MENULAR MELALUI KONTAK SEKSUAL ? (PERDOSKI, 2022)
The widespread Covid-19 outbreak has raised many questions about the origin and transmission of the virus. It has now been proven that it can be transmitted through droplets, physical contact and aerosols. Additionally, several other possible modes of transmission are being explored. The discovery of SARS-CoV-2 and ACE2 in male and female reproductive organs, raises suspicions of the possibility of transmitting Covid-19 through sexual contact. The main purpose of this paper is to review the existing literature on possible modes of transmission of Covid-19, primarily through sexual contact; also to develop an understanding of the causes and spread of SARS-CoV-2, and to suggest recommendations for containing and preventing the spread of new coronavirus. An assessment of possible modes of transmission of SARS-CoV-2 was carried out based on reports and articles available on PubMed and ScienceDirect.com with keywords, ‘transmission’, ‘sexual contact’, ‘Coronavirus’, ‘SARS-CoV-2’, and ‘Covid-19’. Various studies have shown different results regarding the presence of SARS-CoV-2 in the reproductive organs of both men and women, some found SARS-Cov-2 in kidney, anal, semen, and vaginal fluids; but some other researchers did not find. Likewise, the existence of the ACE2 receptor in the reproductive organs as a receptor that determines a person's susceptibility to infection, the results are controversial. A long study is still needed to be able to conclude whether Covid-19 can be transmitted through sexual contact. The experts advise someone affected by Covid-19 to postpone close contact, including sexual contact, always maintain personal and environmental hygiene, also adhering to health protocols.